Pembukaan Rahasia Bank Oleh Pusat Pelaporan Dan Analisis Transaksi Keuangan Sebagai Upaya Pemberantasan Tindak Pidana Pencucian Uang - Siti Nurjanah; Andry Andry (Fakultas Hukum, Universitas Internasional Batam, 2015)
Along with the times growing, it is necessary for a specific law to regulate and supervise economic activity in a country, especially in the banking sector which providing bank services. It is known that the bank is an institution that upholds the trust of customers on financial secrecy customers are categorized as bank secrecy so as to make the bank a target to commit criminal acts of money laundering. For the sake of prevention and eradication of money laundering, the government issued Law No. 8 of 2010 on the Prevention and Combating Money Laundering and forming institutions Analysis of Financial Transactions Reporting Center has the authority to require the reporting of customer transactions is strictly confidential.This study is a normative legal research using normative juridical. Data used in the form of secondary data. Data mining is done with literature (library research) and interview. Once all the data is collected, the data is then processed and analyzed, the qualitative analysis was used to group the data point to the aspects studied. Furthermore, the conclusions drawn related to this research, then elaborated descriptivelyBased on this study showed that in dealing with money laundering INTRAC play an important role by conducting an investigation of the transaction reports from banks and do reports on analysis results which indicate laundering to the authorities to deal with such offenses.